2014
DOI: 10.1007/s00170-014-6563-3
|View full text |Cite
|
Sign up to set email alerts
|

A new process of forming metallic bipolar plates for PEM fuel cell with pin-type pattern

Abstract: Bipolar plates are the most important and expensive components of a fuel cell. These plates can be fabricated by different processes, such as machining graphite plates, producing composite materials, and forming metallic sheets. Due to some benefits of the metallic plates, especially with stainless steel sheets, they have recently been more noticeable. There are various flow field patterns with different applications in these plates, being classified into simple and complex ones in forming process for spiral o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Since the process is performed at high temperature, the applied pressure is too low in comparison to the other methods. As an illustration, achieving to the filling percentage of 80%, the applied pressure in hydroforming method [16] is about 50 MPa and in HMGS is 4 MPa. Although the material properties and the thickness of blank in their study are different, the pressure is utilized in HMGS is considerably lower than the other methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the process is performed at high temperature, the applied pressure is too low in comparison to the other methods. As an illustration, achieving to the filling percentage of 80%, the applied pressure in hydroforming method [16] is about 50 MPa and in HMGS is 4 MPa. Although the material properties and the thickness of blank in their study are different, the pressure is utilized in HMGS is considerably lower than the other methods.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported the optimal shape for aluminum bipolar plate. Belali-Owsia et al [16] applied hydroforming, stamping and hybrid hydroforming-stamping method in order to forming of pin-type pattern bipolar plates. Ghadikolaee et al [17] studied about various parameters of rubber pad forming, such as applied pressure, hardness and thickness of rubber pad in order to achieve the deepest channels before fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the height to width ratio of a flow channel has an essential impact on the performance of a fuel cell. Belali-Owsia et al [10] fabricated a pin-shaped bipolar plate from the SS304 steel sheet using three different methods of hydroforming, stamping, and hybrid hydroforming-stamping. Mohammadtabar et al [11] examined the feasibility of a double-step hydroforming process to make a bipolar plate with a serpentine channel flow field.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] As one key component in the PEMFC, the bipolar plate connects each cell electrically, supplies reactant gases to both anode and cathode, and removes reaction products from the cell. [9,10] Up to now, bipolar plates of stainless steels, [11][12][13][14][15][16][17][18][19][20][21] aluminum alloys, [22][23][24][25][26][27] titanium alloys, [28][29][30] bulk metallic glasses, [31] copper alloys, [32] and nickel alloys [33] have been manufactured by stamping or hydroforming processes. [5,6] Metallic bipolar plates have been the first choice because they not only offer desirable characteristics (high electrical conductivity, formability and manufacturability, gas impermeability, and superior mechanical properties), [7,8] but also higher strength, toughness, and shock resistance than those of graphitic or composite bipolar plates.…”
Section: Introductionmentioning
confidence: 99%
“…Although metals offer many advantages, they are more susceptible to corrosion, which can adversely affect their performance and durability. [9,10] Up to now, bipolar plates of stainless steels, [11][12][13][14][15][16][17][18][19][20][21] aluminum alloys, [22][23][24][25][26][27] titanium alloys, [28][29][30] bulk metallic glasses, [31] copper alloys, [32] and nickel alloys [33] have been manufactured by stamping or hydroforming processes. Compared to single metal sheet, metal clad sheets offer a cost effective approach for bipolar plates which integrate the advantages and avoid the disadvantages of these two groups of metals.…”
Section: Introductionmentioning
confidence: 99%